THE ROLE OF SERVICE QUALITY AND DIGITAL BANKING IN ENHANCING CUSTOMER LOYALTY THROUGH CUSTOMER ENGAGEMENT AS AN INTERVENING VARIABLE (A STUDY ON EMPLOYEES OF PT BANK BNI PEKALONGAN CITY BRANCH OFFICE) - Bagas Setyadi; Alimuddin Rizal Rivai (SOSIOEDUKASI, 2026)
This study primarily seeks to investigate how Service Quality and Digital Banking contribute to Customer Loyalty, accompanied by Customer Engagement performing as a central mediation pathway. Data was gathered from 100 customers at the Pekalongan City Branch Office of PT Bank BNI. A quantitative approach was employed, utilizing survey questionnaires for data collection, and SPSS software facilitated the analysis of the collected information. The findings confirm that all seven hypotheses receive positive and significant support. Service Quality positively influences Customer Engagement (coefficient 0.243, significance 0.012). Digital Banking also shows a positive impact on Customer Engagement (coefficient 0.479, significance 0.000). Service Quality meaningfully impacts Customer Loyalty (coefficient 0.448, significance 0.000). Digital Banking exhibits a favorable association with Customer Loyalty (coefficient 0.416, significance 0.001). Customer Engagement significantly predicts Customer Loyalty (coefficient 0.601, significance 0.016). The Sobel Test outcome verifies that Customer Engagement functions as a key channel of mediation among Service Quality and Customer Loyalty, alongside the linkage between Digital Banking and Customer Loyalty. The managerial implication of this study emphasizes that consistent improvement in service quality and robust digital banking infrastructure will increase emotional engagement, which in turn strengthens long-term customer loyalty. The study enhances scholarly perspectives on the formulation of service strategies and digital transformation in the banking industry in an increasingly competitive era.